Pengaruh IkIan (Televisi Dan Radio) Terhadap Minat Bell Konsumen (Study Kasus Pada Produk Sepeda Motor Merek Honda Di Wilayah Kecamatan Bandar Sribhawono) - Lestari Wuryanti (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2014)
Abstract. The growth of the automotive business will be able to improve the welfare of the actors, especially the automotive business and the growing interest of consumers and potential consumers if the manufacturer knows about what the consumer wants, for that we need a strategy that should run the company, particularly in the field of marketing. One strategy used by companies of Honda motorcycles in order to attract consumers to the product is through advertising. As the growth of the economy, advertising becomes very important because potential customers will pay attention to advertising of products she would buy. Advertising function other than as a promotion also serves to inform a product or service or company profits and as media to remind consumers of a product or service. The purpose of this study was to prove whether ads on television and radio significantly influence consumers to buy the products of Honda motorcycles in districts of Bandar Sribhawono. The analysis tool used is the analysis of qualitative and quantitative analysis using manual calculation and SPSS (Statistical Packages for Social Sciences) 16. Based on the calculation, the results obtained from the influence of advertising on television and radio on consumer buying interest Honda motorcycle products in the region Bandar Sribhawono districts is significant as evidenced by the calculation of SPSS 16 with a probability of 0.000 <0.05 then H0 rejected and Haaccepted.